Negociando a vida e a morte: estado, igreja e crime em uma favela de Belo Horizonte - Beraldo, Ana (2020)
This thesis deals with dynamics of life and death at the margins. Based on fieldwork carried out in a large slum in the city of Belo Horizonte, here called Morro da Luz, an analysis is made about the coexistence of different regulatory regimes in territories in the urban periphery, that is, the interaction between different logics, morally informed, to organize symbolically and materially the relations of sociability and the classifications of what is or is no longer socially acceptable, desired or disapproved. Throughout the text, it is demonstrated that, currently, there are three main normative regimes operating in Luz and, possibly, in other similar territories throughout Latin America: state (in its multiple and often antagonistic facets); crime (which, in Belo Horizonte, is characterized by the presence of several small groups that compete with each other, but which are still capable of building a criminal discourse unit); and church (especially the many evangelical strands). These three normativities build symbolic relationships among themselves that alternate between dispute and articulation, forming a normative triangulation that acts, based on the sharing of the appreciation of the notion of respectability, as a mechanism for the daily moral analysis of people and behaviors. These dynamics are made possible by a broader scenario, typical of post-colonial nations, of production and maintenance of economic and rights inequalities, which, in the favela, make subjects in an eternal negotiation between life and death.